Performance and genetic variability of onion cultivars in the coastal region of Bangladesh (Bangladesh Journal of Botany, 2026)
Evaluation of the growth and yield attributes of four onion cultivars, in the coastal area were studied. Among the evaluated cultivars, Lal Teer king demonstrated superior performance under saline conditions, recording the highest values for plant height (50.43 cm), number of leaves (10.74), leaf length (37.27 cm), bulb diameter (4.53 cm), bulb length (4.62 cm), individual bulb weight (33.58 g), yield per plot (1410.5 g), and yield per hectare (14.11 t ha⁻¹). Correlation analysis revealed positive associations among key vegetative and yield-related traits. Furthermore, the genetic parameter estimates and principal component analysis (PC1–PC3) indicated substantial genetic variability and the potential for genetic improvement. Therefore, Lal Teer king may be considered a promising cultivar for onion production and future breeding programs aimed at improving salinity tolerance in the coastal region of Bangladesh.Bangladesh J. Bot. 55(2): 287-293, 2026 (June)